The Venturesome Economy : How Innovation Sustains Prosperity in a More Connected World - Bhide, Amar, 1955- (Book collections on Project MUSE., 2008)
Many warn that the next stage of globalization--the offshoring of research and development to China and India--threatens the foundations of Western prosperity. But in The Venturesome Economy, acclaimed business and economics scholar Amar Bhide shows how wrong the doomsayers are. Using extensive field studies on venture-capital-backed businesses to examine how technology really advances in modern economies, Bhide explains why know-how developed abroad enhances--not diminishes--prosperity at home, and why trying to maintain the U.S. lead by subsidizing more research or training more scientists w.